β-Elemene Synergizes With Gefitinib to Inhibit Stem-Like Phenotypes and Progression of Lung Cancer via Down-Regulating EZH2 - Cheng, Haibo; Ge, Xiaoyin; Zhuo, Shiqin; Gao, Yanan; Zhu, Bo; Zhang, Junfeng; Shang, Wenbin; Xu, Dakang; Ge, Weihong; Shi, Liyun (Frontiers in Pharmacology, 2018)
The inhibitors for EGF receptor tyrosine kinase (EGFR-TKIs) such as gefitinib have been used as a standard treatment for non-small cell lung cancer (NSCLC), but the increasingly occurrence of drug resistance, the associated adverse effects and the enrichment of cancer stem cells significantly impedes its clinical application. β-elemene is a natural sesquiterpene with potent anti-cancer ability, and also it is renowned for its plant-origin, safety and the additive effect with traditional therapies, which prompt us to explore its potential to co-operate with TKIs to achieve greater therapeutic efficacy. Impressively, our study demonstrates that, elemene, in combination of gefitinib, displayed a significantly higher activity in inhibiting lung cancer cellular proliferation, migration and invasion. More importantly, combinative treatment profoundly impaired the epithelial to mesenchymal transition (EMT), the stem-like properties and the self-renewal capacity of lung cancer cells, and hence impeded the in vivo tumor development. We also reveal that the synergistic anti-tumor effect of elemene and gefitinib was largely mediated their regulation of enhancer of zeste homolog 2 (EZH2), an oncogenic histone methytransfelase and gene transcriptional regulator. Thus, our data indicate that combinative treatment of elemene and gefitinib has greater anti-neoplastic activity and greater efficacies in targeting cancer stem-like properties, mainly through regulating the malignant gene modifier and hence the subsequent effector molecules required for cancer progression. The findings may have potential implications for treating aggressive and resistant lung cancers.